Active detection of tuberculosis: tackling the problem head on in the remote area of Andaman and Nicobar Islands - Burma, Samarendra Prasanna; Jahnavi, Gunda; Lal, Pappachen; Thatkar, Pandurang V. (International Journal Of Community Medicine And Public Health, 2019)
Background: Community based active case finding for tuberculosis (TB) is an essential step in the fight forward for eliminating TB. One of the steps in targeting TB intervention is early diagnosis and treatment of patients by reducing the reservoir of infection in the community. Active case finding (ACF) targeting the entire population by house to house survey was done in Nicobar district of these islands. Methods: A community-based, cross-sectional, descriptive study was conducted with the trained mobile teams from 17.07.2017 to 31.07.2017 in the Nicobar District. The algorithm of the case detection included screening patients by symptoms, then by sputum microscopy for confirmation. X-ray was done in patients who were symptomatic but sputum negative. If both smear and chest X-ray results were negative but still symptomatic, then cartridge-based nucleic acid amplification test (CBNAAT) was done. Results: A total population of 18526 was mapped of which 14784 (79.8) could be screened. A total of 209 people were identified by the mobile teams with symptoms who were examined by sputum microscopy. Among them 7 cases were identified to be sputum smear positive, 2 X-ray positive and 2 were diagnosed by CBNAAT. Conclusions: This study shows that the active case finding method is feasible and acceptable by the community. The results obtained are encouraging for the implementation of ACF through mobile team activity in all these islands in order to meet the target of WHO’s End TB Strategy.